Manajemen Program Usaha Kesehatan Sekolah/Madrasah (UKS/M) Oleh Pemerintah Kota Payakumbuh Dalam Mewujudkan Kota Sehat - Putri, Cecilya Asmarani Oka; Putera, Roni Ekha; Yoserizal, Yoserizal (LPPM Universitas Ekasakti, 2023)
Management of School/Madrasah Health Program (UKS/M) by Payakumbuh City Government in Realizing Healthy City in 2017. In running a program, a management process is needed to run according to plan. Careful planning can determine the effectiveness of an activity. For the implementation of a Healthy School that is sustainable, smooth, and good, good planning is also needed by the Payakumbuh City Government. Objective: to describe and analyze the Management of the School/Madrasah Health Program (UKS/M) by the Payakumbuh City Government in realizing a Healthy City in 2017. Method: this research is qualitative with a descriptive research type. Results/Findings: Through planning, organizing, directing, and supervision, it shows that the management carried out by the Payakumbuh City Government is running according to plan, but there are still obstacles in its implementation, such as the lack of supervision carried out on the community or canteen traders who sell unhealthy food, and the lack of participation of the community living around the school environment in realizing a clean and healthy environment.